Influence of nanoparticle fillers content on the bearing strength behavior of glass fiber-reinforced epoxy composites pin joints. (December 2017) - Sekhon, Manjeet; Saini, JS; Singla, Gaurav; Bhunia, H
The objective of the present study is to investigate and compare the strength of single pin joints made with glass fiber-reinforced epoxy laminates containing two different nanoparticles, i.e. nanoclay and nano TiO2, with bare composites. The analysis has been done both experimentally and numerically. Single-hole pin-loaded specimens were tested for their tensile strength and the distance from the free edge of the specimen to the diameter of the first hole (E/D) ratio, width of the specimen to the diameter of the holes (W/D) ratio were evaluated. The influence of these geometry parameters on the strength of the pin-loaded composites was investigated. It was found that the bearing strength of pin joints increased with the addition of nanoclay as compared to that of nano TiO2 .